Natural rubber toughened and modified polylactic acid and preparation method thereof
The melt blending method directly prepares natural rubber toughened modified polylactic acid materials, which solves the problem of poor compatibility between natural rubber and polylactic acid, achieves the improvement of the mechanical properties of the material and the low-temperature toughening effect, simplifies the preparation process and has environmentally friendly characteristics.
Patent Information
- Application Number
- CN202411724940.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-04
AI Technical Summary
The poor compatibility between existing natural rubber and polylactic acid leads to poor performance in mechanical properties, thermal stability and processing properties of composite materials, which is difficult to meet the needs in practical applications.
The natural rubber toughened modified polylactic acid material is directly prepared by melt blending without pretreatment of the material. The raw material ratio and blending conditions are optimized, including temperature, time and rotation speed to improve the compatibility and comprehensive performance of the material.
It has achieved significant improvements in the mechanical properties and low-temperature toughening effect of materials, simplified the preparation process, reduced production costs and step complexity, is suitable for large-scale industrial applications, and is characterized by environmental protection and sustainable development.
Smart Images

Figure BDA0005158980080000021 
Figure BDA0005158980080000031 
Figure BDA0005158980080000032
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials, and in particular to a natural rubber toughened and modified polylactic acid and a preparation method thereof. Background Art
[0002] Polylactic acid (PLA) is a high molecular polymer made from green plants. It is made by decomposing the raw materials into glucose, fermenting them to generate lactic acid, and polymerizing the lactic acid. Its physical and chemical properties are similar to those of traditional thermoplastics. However, compared with traditional plastics, it has better biodegradability and will not cause pollution and damage to the environment, solving the energy consumption and environmental pollution problems caused by the processing of traditional plastics.
[0003] In addition to its excellent biodegradability, PLA's good processability and good mechanical properties have led to its extensive research and application. In the biomedical field, PLA can be used to produce disposable medical tools, which can reduce environmental pollution after disposal. Because of its certain biocompatibility and mechanical strength, it can be used to manufacture non-removable surgical sutures and artificial bone tissue. However, PLA materials have problems such as high brittleness, poor toughness, lack of elasticity, general fluidity and slow degradation. These defects limit many industrial applications of PLA, especially industrial and medical applications that require good plastic deformation capabilities under high stress levels. Therefore, in order to further broaden the scope of application of PLA, it is necessary to perform appropriate physical or chemical modifications on it so that it can meet different usage requirements.
[0004] In the current technical field, there have been many studies and published literature reports on various methods, including modifying polylactic acid (PLA) by introducing natural rubber.
[0005] For example, Chinese patent CN102276965A discloses a method for toughening and modifying polylactic acid. A toughened polylactic acid system is obtained by using natural rubber as a toughening agent. Peroxide is used as an initiator to initiate crosslinking of the system, thereby enhancing the toughening effect of natural rubber on polylactic acid. In the toughened polylactic acid system, polylactic acid is 70-95 parts, natural rubber is 5-30 parts, and peroxide initiator is 0.2-1 parts. The toughened polylactic acid material is obtained by mixing.
[0006] However, as an elastomer, natural rubber is not ideally compatible with polylactic acid. Due to this poor compatibility, the interfacial bonding between natural rubber and polylactic acid is weak during the preparation process, which results in certain limitations in the performance of the composite materials finally prepared. These materials may perform poorly in terms of mechanical properties, thermal stability, and processing performance, and are difficult to meet the needs of practical applications. Therefore, in order to further improve the comprehensive performance of these modified materials, it is urgent to improve and optimize the compatibility between natural rubber and polylactic acid.
[0007] In the current technical field, the scheme of pre-modifying natural rubber is generally adopted to improve its compatibility with polylactic acid (PLA). For example, Chinese patent CN117511152A discloses an environmentally friendly polylactic acid plastic and its preparation method and application. The preparation method of the environmentally friendly polylactic acid plastic includes crushing the eugenol grafted modified natural rubber and mixing it with polylactic acid, the mixer temperature is 180°C, the speed is 60rpm, after mixing for 5 minutes, adding a nucleating agent and a vulcanizing agent, and continuing to mix for 10 minutes to obtain a preform. In this step, the mass ratio of eugenol grafted modified natural rubber: polylactic acid: nucleating agent: vulcanizing agent is 8:100:0.05:0.04; the preform is transferred to an injection molding machine for injection molding to obtain an environmentally friendly polylactic acid plastic.
[0008] However, in the actual production process, this method has the problems of high cost and cumbersome steps, which makes it face many challenges in its wide application. Specifically, the pre-modification treatment of natural rubber usually requires complex chemical reactions and delicate operation steps, which not only increases the production cost, but also prolongs the production cycle. In addition, due to the large fluctuations in the source and quality of natural rubber, its modification effect is difficult to maintain consistency, which further limits its application in large-scale production. Therefore, finding a modification method with lower cost and simpler steps to improve the compatibility of natural rubber and PLA has become an urgent problem to be solved in the field of materials. Summary of the invention
[0009] The object of the present invention is to provide a natural rubber toughened modified polylactic acid and a preparation method thereof, which can prepare a modified material with excellent performance by melt blending without pre-treating the material. The method not only gives the material excellent mechanical properties, but also achieves a toughening effect under low temperature conditions.
[0010] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0011] The present invention provides a natural rubber toughened and modified polylactic acid material, which is made of the following raw materials in parts by weight:
[0012]
[0013]
[0014] Preferably, it is made from the following raw materials in parts by weight:
[0015]
[0016] The present invention also provides a method for preparing the natural rubber toughened and modified polylactic acid material, comprising the following steps:
[0017] All materials are blended to obtain natural rubber toughened and modified polylactic acid material.
[0018] Preferably, the blending is performed by melt blending.
[0019] Preferably, the equipment used in the melt blending method is an internal mixer.
[0020] Preferably, the temperature of the melt blending method is 150-250°C.
[0021] Preferably, the melt blending process is carried out for 10 to 30 minutes.
[0022] Preferably, the rotation speed of the melt blending method is 50 to 100 rpm.
[0023] Preferably, the blending further comprises extrusion molding;
[0024] The thickness of the extrusion molding is 0.1 to 10 mm.
[0025] The present invention also provides the use of the natural rubber toughened modified polylactic acid material, or the natural rubber toughened modified polylactic acid material prepared by the above preparation method in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.
[0026] Technical effects and advantages of the present invention:
[0027] The method for toughening and modifying polylactic acid with natural rubber provided by the present invention does not require any pretreatment steps for the raw materials, and can directly prepare a modified material with excellent performance by melt blending. The preparation method provided by the present invention is simple, and the operation steps are simple and easy to perform, so it is very suitable for large-scale industrial applications. The production process does not require complex equipment or difficult technology. The entire preparation process is efficient and economical, and has high practicality and broad application prospects in industrial production.
[0028] The natural rubber toughened modified polylactic acid material provided by the present invention not only has excellent mechanical properties, but also exhibits good toughening effect under low temperature conditions. Generally, modified polylactic acid materials become brittle and easy to break under low temperature conditions, while the modified material provided by the present invention can maintain good flexibility and impact resistance under low temperature conditions, making it have a wide range of application prospects in cold environments.
[0029] The natural rubber toughened modified polylactic acid solution provided by the present invention also has the characteristics of environmental protection and sustainable development. Since polylactic acid is a biodegradable polymer derived from renewable resources, its production and use have little impact on the environment. Natural rubber, as a natural polymer material, also has the characteristics of being renewable and degradable. The present invention uses these two materials as the main materials for preparation, which not only improves the comprehensive performance of the material, but also further enhances its environmental protection attributes.
[0030] The natural rubber toughening and modified polylactic acid method provided by the present invention not only simplifies the material preparation process, but also gives the material excellent mechanical properties and low-temperature toughening effect, while having the advantages of environmental protection and sustainable development, and has broad application prospects and market potential. DETAILED DESCRIPTION
[0031] The present invention provides a natural rubber toughened and modified polylactic acid material, which is made of the following raw materials in parts by weight:
[0032]
[0033] Preferably, it is made from the following raw materials in parts by weight:
[0034]
[0035]
[0036] In the present invention, the polylactic acid, also known as polylactide (PLA), is a polyester polymer obtained by polymerization with lactic acid as the main raw material. It is a new type of biodegradable material with good solvent resistance and can be processed in a variety of ways, such as extrusion, spinning, biaxial stretching, and injection blow molding. In addition to being biodegradable, the products made of polylactic acid have good biocompatibility, gloss, transparency, feel and heat resistance. The polylactic acid used in the embodiment of the present invention is in liquid form, CAS No.: 26023-30-3, purchased from Bashifu (Shanghai) Biomedical Technology Co., Ltd.
[0037] In the present invention, the natural rubber (NR) is a natural polymer compound with cis-1,4-polyisoprene as the main component, 91% to 94% of its components are rubber hydrocarbons (cis-1,4-polyisoprene), and the rest are non-rubber substances such as proteins, fatty acids, ash, and sugars. It is the most widely used general-purpose rubber. The natural rubber used in the embodiments of the present invention is purchased from the market; it is dried to a moisture content of less than 5% before use.
[0038] In the present invention, chitosan is a long-chain polymer, which is polymerized from N-acetylglucosamine, a derivative of glucose, as a monomer. It is a translucent, flexible, elastic and very tough substance in nature. Chitosan, also known as chitin, is a polysaccharide extracted from the shells of marine crustaceans, and its chemical formula is (C8H 13 O5N) n . Chitosan is light beige to white, soluble in concentrated hydrochloric acid, phosphoric acid, sulfuric acid and acetic acid, insoluble in alkali and other organic solvents, and insoluble in water. The deacetylated derivative of chitosan, chitosan, is insoluble in water but soluble in some dilute acids. Chitosan has a wide range of applications. In industry, it can be used to make cloth, clothing, dyes, paper and water treatment. In agriculture, it can be used as pesticides and plant antiviral agents. In fisheries, it can be used as fish feed. Cosmetic beauty agents, hair protectors, moisturizers, etc. In medical supplies, it can be used to make contact lenses, artificial skin, sutures, artificial dialysis membranes and artificial blood vessels. The chitosan used in the embodiments of the present invention is in powder form, CAS No.: 1398-61-4, purchased from Jiangsu Caiwei Biotechnology Co., Ltd.
[0039] In the present invention, the polycaprolactone is an organic high molecular polymer with the chemical formula (C6H 10 O2) n , which has the property of being well soluble in aromatic compounds, ketones and polar solvents. It is prepared by ring-opening polymerization of ε-caprolactone under the conditions of metal organic compounds (such as tetraphenyltin) as catalyst and dihydroxy or trihydroxy as initiator. It belongs to polymerized polyester, and its molecular weight and disproportionation degree vary with the type and amount of starting materials. The PCL raw material used in the embodiment of the present invention is in the form of translucent plastic particles, which is a blown film extrusion grade product purchased from Dongguan Baojia Plastic Co., Ltd.
[0040] In the present invention, the polyisobutylene (PIB) is a polymer obtained by cationic polymerization of isobutylene, and its molecular weight can range from hundreds to millions. It is a typical saturated linear polymer, the main body of the molecular chain does not contain double bonds, and there is no long branch chain. Its structural unit is -(CH2-C(CH3)2)-, in which there is no asymmetric carbon atom, and the structural units are connected in a regular sequence from head to tail. The polyisobutylene used in the embodiment of the present invention: CAS No.: 9003-27-4, purchased from Guangzhou Jinglong Technology Co., Ltd.
[0041] In the present invention, the dioctyl phthalate is a colorless transparent liquid with a specific gravity of 0.9861 (20 / 20), a melting point of -50°C, a boiling point of 386°C (normal pressure), insoluble in water, and soluble in most organic solvents such as ethanol, ether, and mineral oil. The dioctyl phthalate used in the embodiments of the present invention, CAS No.: 117-84-0, was purchased from Jinan Zekuan Chemical Co., Ltd., and the relevant experiments were carried out under the laboratory safety supervision and management regulations.
[0042] In the present invention, the triphenyl phosphite is an organic compound with the chemical formula C 18 H 15 O3P is mainly used as an antioxidant stabilizer for high molecular polymers such as polyethylene, polypropylene, polyvinyl chloride, ABS resin, epoxy resin, synthetic rubber and polyester in the prior art. Triphenyl phosphite used in the embodiment of the present invention has a CAS number of 101-02-0 and is purchased from Shandong Binteng Chemical Co., Ltd.
[0043] In the present invention, by carefully designing and selecting a specific raw material ratio, the optimal performance of the natural rubber toughened modified polylactic acid blend can be effectively achieved. This ratio ensures that the various raw materials can play the best synergistic role in the blend, thereby achieving the expected material performance. Specifically, the amount of each raw material is accurately calculated to ensure that their proportion in the blend is just right. If the amount of some of the raw materials is too high, some performance of the blend may be reduced, or even incompatible, thereby affecting the overall performance of the material. On the contrary, if the amount of some raw materials is too low, they may not be able to fully play their due role, resulting in the performance of the blend failing to reach the optimal state. Therefore, only under the premise of strictly controlling the amount of raw materials, can it be ensured that the blended material in the present invention can show excellent effects and meet various application requirements.
[0044] The present invention also provides a method for preparing the above-mentioned natural rubber toughened modified polylactic acid material, comprising the following steps: all materials are blended to obtain a natural rubber toughened modified polylactic acid material. Preferably, the blending adopts a melt blending method. Preferably, the equipment used in the melt blending method is an internal mixer. Preferably, the temperature of the melt blending method is 150 to 250°C. Preferably, the time of the melt blending method is 10 to 30 minutes. Preferably, the rotation speed of the melt blending method is 50 to 100 rpm. Preferably, after the blending, extrusion molding is also performed; the thickness of the extrusion molding is 0.1 to 10 mm.
[0045] In the present invention, the parameters such as temperature, time and rotation speed of the melt blending method are optimized to ensure that the materials can be fully mixed during the blending process and avoid the degradation of material properties due to overheating. The temperature of the melt blending method is controlled within the range of 150 to 250°C, which can ensure that materials such as polylactic acid and natural rubber can fully flow and mix in a molten state to form a uniform blend. The blending time is controlled within 10 to 30 minutes to ensure that there is enough time for the raw materials to interact physically and chemically, thereby achieving the desired modification effect. The rotation speed is controlled within 50 to 100 rpm to ensure that the shear force during the mixing process is moderate, which can promote the dispersion and mixing of the raw materials without causing excessive shear damage to the materials.
[0046] In the present invention, the extrusion molding step is performed after blending, and the purpose is to further process the blend into a desired shape and size. The thickness of the extrusion molding is controlled at 0.1 to 10 mm, which can meet the requirements of material thickness in different application fields. Through extrusion molding, a modified polylactic acid material with a specific shape and size can be obtained, which is convenient for subsequent processing and application.
[0047] The present invention also provides the use of the natural rubber toughened modified polylactic acid material, or the natural rubber toughened modified polylactic acid material prepared by the above preparation method in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.
[0048] The application of the natural rubber toughened modified polylactic acid material of the present invention in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing can provide excellent mechanical properties and low-temperature toughening effects, and has the advantages of environmental protection and sustainable development. For example, in automobile manufacturing, the material can be used to manufacture interior parts, body parts, etc., which not only reduces the weight of the vehicle, but also reduces the impact on the environment. In the field of aerospace, the material can be used to manufacture lightweight, high-strength structural parts to improve the performance of aircraft. In electronic equipment manufacturing, the material can be used to manufacture parts such as housings and brackets, providing good impact resistance and durability. In industrial equipment manufacturing and packaging material manufacturing, the material can provide environmentally friendly, degradable substitutes to reduce the pollution of plastic waste to the environment.
[0049] The application of the present invention in automobile manufacturing is preferably used to manufacture automobile shells, interior trims, suspension systems, engine parts, front-end modules, instrument panel frames, door modules, etc.
[0050] The application of the natural rubber toughened modified polylactic acid material in aerospace is preferably used to reduce weight, thereby improving fuel efficiency and load capacity, making the aircraft lighter and more efficient, and to improve safety and protect internal electronic components from damage; used to enhance structural strength: the application of toughened plastics in aerospace structural parts, such as aircraft wings, fuselages, etc., can significantly improve the strength and toughness of the structure and reduce the risk of damage caused by external impact.
[0051] The application of the natural rubber toughened modified polylactic acid material in electronic devices is preferably used to enhance the mechanical properties of electronic devices and reduce the risk of damage to the devices when subjected to external force impact, such as mobile phone protective cases and headphone cables, which can effectively buffer the impact force and reduce the damage to the devices caused by falling or collision; used to improve safety and prevent wear and tear; used to extend the service life of electronic devices, effectively protect the internal wires from the influence of the external environment, and ensure the long-term stability and safety of the equipment
[0052] The application of the natural rubber toughened modified polylactic acid material of the present invention in the manufacture of industrial appliances is preferably to increase the environmental performance and service life of the appliances.
[0053] The application of the natural rubber toughened modified polylactic acid material in the manufacture of packaging materials is preferably to improve brittleness: significantly reduce the brittleness of the packaging material, so that it is not easy to break during transportation and storage, and extend the service life; improve impact resistance: when subjected to external force impact, it can absorb more energy to prevent the packaging material from breaking and protect the internal items from damage; enhance durability: the packaging material can still maintain good physical properties after multiple uses, reduce the frequency of replacement, and reduce the overall cost; improve safety: it is not easy to break when impacted, reducing the safety hazards caused by the rupture of the packaging material and ensuring the safety of users.
[0054] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0055] Example 1
[0056] Weigh the following raw materials by weight and mix them evenly:
[0057]
[0058]
[0059] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0060] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0061] Example 2
[0062] Weigh the following raw materials by weight and mix them evenly:
[0063]
[0064] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0065] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0066] Example 3
[0067] Weigh the following raw materials by weight and mix them evenly:
[0068]
[0069] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 220° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0070] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0071] Example 4
[0072] Weigh the following raw materials by weight and mix them evenly:
[0073]
[0074] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 180° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0075] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0076] Example 5
[0077] Weigh the following raw materials by weight and mix them evenly:
[0078]
[0079] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0080] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0081] Example 6
[0082] Weigh the following raw materials by weight and mix them evenly:
[0083]
[0084] All raw materials were put into an internal mixer for melt blending at a speed of 70 rpm and a temperature of 200° C. for 30 min to obtain a natural rubber toughened and modified polylactic acid material.
[0085] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0086] Example 7
[0087] Weigh the following raw materials by weight and mix them evenly:
[0088]
[0089] All raw materials were put into an internal mixer for melt blending at a speed of 50 rpm and a temperature of 180° C. for 15 min to obtain a natural rubber toughened modified polylactic acid material.
[0090] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0091] Example 8
[0092] Weigh the following raw materials by weight and mix them evenly:
[0093]
[0094]
[0095] All raw materials were put into an internal mixer for melt blending at a speed of 100 rpm and a temperature of 200° C. for 20 minutes to obtain a natural rubber toughened modified polylactic acid material.
[0096] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0097] Example 9
[0098] Weigh the following raw materials by weight and mix them evenly:
[0099]
[0100] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0101] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0102] Example 10
[0103] Weigh the following raw materials by weight and mix them evenly:
[0104]
[0105]
[0106] All raw materials were put into an internal mixer for melt blending at a speed of 100 rpm and a temperature of 200° C. for 20 minutes to obtain a natural rubber toughened modified polylactic acid material.
[0107] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0108] Comparative Example 1
[0109] Weigh the following raw materials by weight and mix them evenly:
[0110]
[0111] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0112] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0113] Comparative Example 2
[0114] Weigh the following raw materials by weight and mix them evenly:
[0115] PLA 100 pieces
[0116] 20 parts of natural rubber
[0117] Chitosan 10 parts
[0118] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0119] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0120] Comparative Example 3
[0121] Weigh the following raw materials by weight and mix them evenly:
[0122]
[0123]
[0124] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0125] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0126] Comparative Example 4
[0127] Weigh the following raw materials by weight and mix them evenly:
[0128] PLA 100 pieces
[0129] 20 parts of natural rubber
[0130] 2 parts of triphenyl phosphite
[0131] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0132] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0133] Comparative Example 5
[0134] Weigh the following raw materials by weight and mix them evenly:
[0135]
[0136] All raw materials were put into an internal mixer for melt blending at a speed of 80 rpm and a temperature of 200° C. for 20 min to obtain a natural rubber toughened modified polylactic acid material.
[0137] The blended material was transferred to a single-screw extruder for extrusion molding with a thickness set to 1 mm and used as a sample for performance testing.
[0138] Experimental example
[0139] The following tests were performed using pure PLA, materials obtained in Examples 1 to 5, and Comparative Examples 1 to 5 as samples:
[0140] Mechanical properties test:
[0141] Use a universal mechanical properties tester to test the tensile properties of the specimens and record the results;
[0142] The sample size is 4mm×1mm, the chuck spacing is 30mm, and the tensile speed is 5mm / min.
[0143] The samples were placed at room temperature for 48 hours before testing.
[0144] The tensile elastic modulus is tested during the tensile test. During the elastic deformation stage of the tensile test, the strain value of the sample under a specific stress is measured and the tensile elastic modulus is calculated using Hooke's law:
[0145] E = σ / ε, where E is the tensile elastic modulus, σ is stress, and ε is strain
[0146] The measurement results are shown in Table 1 below:
[0147] Table 1 Mechanical properties test results
[0148]
[0149] It can be seen from the mechanical property test results in Table 1 that the natural rubber toughened modified polylactic acid material provided by the present invention is superior to pure PLA and the materials in the comparative example in terms of elongation at break, tensile strength and tensile elastic modulus. The materials of Examples 1 to 5 are significantly improved in elongation at break, all exceeding 84%, achieving significant progress compared with pure PLA. In terms of tensile strength, the materials of the embodiments also show higher strength, all exceeding 132MPa, while pure PLA is only 52.13MPa. These results show that by adding natural rubber, chitin, polycaprolactone, polyisobutylene and a specific ratio of plasticizer and stabilizer in the present invention, the mechanical properties of polylactic acid materials can be effectively improved, making them more suitable for practical applications.
[0150] Impact toughness test:
[0151] The cantilever beam impact tester detects the impact toughness of the specimen and records the results;
[0152] The sample specifications are 80mm×10mm×4mm, the impact energy is 5.5J, the pendulum pre-lift angle is 150°, and the impact speed is 3.5m / s.
[0153] The samples were placed at room temperature for 48 hours before testing.
[0154] The measurement results are shown in Table 2 below:
[0155] Table 2 Impact toughness test results
[0156]
[0157] As shown in Table 2, the polylactic acid material provided by the present invention is superior to pure PLA and the materials in the comparative example in terms of impact toughness. The materials in Examples 1 to 5 have significantly improved impact toughness compared to pure PLA. The materials in the examples show higher impact toughness, which is significantly better than the comparative example.
[0158] After being placed in a low temperature (-20°C) environment for 10 hours, the samples were taken out and mechanical tests were performed in the same manner as above. The results are shown in Table 3:
[0159] Table 3 Mechanical properties test results
[0160]
[0161]
[0162] According to the data analysis results of Table 3 above, after freezing treatment, the modified material provided by the present invention shows a slight downward trend in mechanical properties. Nevertheless, its performance remains at a high level and can still be considered to be excellent. However, after the same freezing treatment, the mechanical properties of the material prepared by the comparative example significantly decrease, and the decrease is large.
[0163] After being placed in a low temperature (-20°C) environment for 10 hours, the samples were taken out and the impact toughness test was performed in the same manner as above. The results are shown in Table 4:
[0164] Table 4 Impact toughness test results
[0165]
[0166]
[0167] According to the data in Table 4 above, after freezing treatment, the modified material provided by the present invention has a slight downward trend in impact toughness. However, its performance remains at a relatively high level and is still a relatively excellent material. However, after the material prepared by the comparative example is subjected to the same freezing treatment, its impact toughness has a significant decrease, and the decrease is relatively large.
[0168] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A natural rubber toughened modified polylactic acid material, characterized in that: Made from the following raw materials in parts by weight:
2. The natural rubber toughened and modified polylactic acid material according to claim 1, characterized in that: Made from the following raw materials in parts by weight:
3. The method for preparing the natural rubber toughened modified polylactic acid material according to claim 1 or 2, characterized in that: The following steps are involved: All materials are blended to obtain natural rubber toughened and modified polylactic acid material.
4. The method for preparing the natural rubber toughened and modified polylactic acid material according to claim 3, characterized in that: The blending is carried out by melt blending.
5. The method for preparing the natural rubber toughened and modified polylactic acid material according to claim 4, characterized in that: The equipment used in the melt blending method is an internal mixer.
6. The method for preparing the natural rubber toughened modified polylactic acid material according to claim 4, characterized in that: The temperature of the melt blending method is 150-250°C.
7. The method for preparing the natural rubber toughened and modified polylactic acid material according to claim 4, characterized in that: The time of the melt blending method is 10 to 30 minutes.
8. The method for preparing the natural rubber toughened and modified polylactic acid material according to claim 4, characterized in that: The rotation speed of the melt blending method is 50-100 rpm.
9. The method for preparing the natural rubber toughened and modified polylactic acid material according to claim 3, characterized in that: The blending further includes extrusion molding; The thickness of the extrusion molding is 0.1 to 10 mm.
10. Use of the natural rubber toughened modified polylactic acid material according to claim 1 or 2, or the natural rubber toughened modified polylactic acid material prepared by the preparation method according to any one of claims 3 to 9 in automobile manufacturing, aerospace, electronic equipment, industrial equipment manufacturing or packaging material manufacturing.
Citation Information
Patent Citations
Method for toughening and modifying polylactic acid by natural rubber
CN102276965A
Environment-friendly polylactic acid plastic as well as preparation method and application thereof
CN117511152A
Toughened polylactic acid compound composition and preparation method thereof
CN105315631A
Polylactic acid material with ultrahigh impact strength and preparation method thereof
CN111534068A
Carapace powder modified polylactic acid composite material and preparation method thereof
CN115678232A